DINAMIKA MANAJEMEN KEUANGAN DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN: Studi Kasus Pada PT Indomarco Prismatama - Hia, Fitri Bevolta Perdamaian; Widagdo, Chrisostomus Susmono (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
PT Indomarco's financial management practices are analyzed using a qualitative descriptive approach to understand the complexity and dynamics of managing financial resources. The study reveals that financial management is a dynamic area that requires a deep understanding of business strategies and the ability to adapt to market changes. This research provides valuable insights for practitioners and academics to develop more effective and responsive financial strategies. Understanding the dynamics of financial management is crucial for achieving optimal financial performance, and PT Indomarco's financial strategies are designed to address these challenges. Thus, PT Indomarco's financial management practices are a testament to the importance of understanding and adapting to market changes.